Comparative assessment of 3D reconstruction technique and Cavalieri’s principle in predicting the mandibular bone defect volumes - Mehmet Ali Altay; Faisal A. Quereshy; Sumit K. Nijhawan; Jose F. Teppa; Michael P. Horan; Nelli Yıldırımyan; Dale A. Baur (European Oral Research, 2018)
Purpose The objective of this study was to compare the accuracy of the Cavalieri’s principle and 3D reconstruction in predicting the volume of a bony defect. Materials and Methods Defects of the same approximate size were created on nine artificial mandibles. The actual volume of the defect on each mandible was measured by water displacement, and served as the control. Each mandible was then scanned using a CBCT and volume measurements were made for each defect using two techniques: Cavalieri’s principle and 3D reconstruction. For each defect, the volume obtained by each of the two techniques was compared to the control volume using the analysis of variances (ANOVA) with p<0.05. Results ANOVA between the control, 3D reconstruction and Cavalieri’s principle groups showed no statistically significant differences (p=.058). When the control group was further analyzed by Dunnett’s post-hoc test, the results from Cavalieri’s principle were found to be statistically different than the control group (p=.035), whereas the results of 3D reconstruction technique did not reach the level of significance (p=.523). Conclusion Cavalieri’s principle significantly underestimates the actual control volume, and is less accurate than the 3D reconstruction technique. The 3D reconstruction method is a reliable technique in measuring volume of bony defects.